Unidad de linealización y normalización para un estimador de parámetros de uso en un sistema de optimización de energía en paneles fotovoltaicos - Cervantes-Segura, Adrián Ignacio (Instituto Tecnológico de Costa Rica, 2016)
Here, the design and veri_cation of an electrical current linealizing module written in Verilog, based on the IEEE 754 oating point standard, and using a CORDIC algorithm to perform a natural logarithm operation is presented. The system is to be used to optimize the e_ciency of photovoltaic panels with a non-linear I-V relation. The design is tested on a Digilint Nexys-4 FPGA board.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electrónica, 2016.
Keywords: Aritmética; Algoritmos; FPGA; Circuitos; Interfaz